Latent profile analysis and influence factors study of presenteeism among ICU nurses in China - Li, Yuxin; Wu, Jijun; Liu, Xiaoli; Zhang, Jiquan; Zhong, Xiaoli; He, Lin (Frontiers in Psychology, 2023)
Background: Presenteeism is a significant global public health problem, and nurses are a highprevalence group of presenteeism, affecting not only nurses' physical and mental health, work efficiency, and quality of work but even poses a serious threat to patient safety.The categorization of presenteeism among ICU nurses is unclear. Our research aims to explore the subtypes of presenteeism among ICU nurses based on latent profile analysis, analyze the influencing factors of different subtypes, and provide a reference basis for developing targeted interventions to reduce the presenteeism rate.Methods: From January to February 2023, 509 ICU nurses in Sichuan Province, China, were selected as respondents and surveyed using the general information questionnaire, the presenteeism scale, and the perceived social support scale. Potential categories of presenteeism among ICU nurses were explored using potential profile analysis, and factors influencing the potential types of presenteeism among ICU nurses were investigated using the chi-square test and multivariate logistic regression analysis.The best model was suggested to consist of three profiles: low presenteeism-normal coping group (18.3%), moderate presenteeism group (47.9%), and high presenteeism-work limitation group (33.8%). Multiple logistic regression results showed that secondary hospitals (OR=0.116, P=0.015), good physical health (OR=0.084, P=0.023), general physical health (OR=0.016, P=0.037), ICU human resource allocation = 1:2.5 to 3 (OR=0.315, P=0.007), and higher social support scores (OR=0.975, P=0.047) were more likely to be grouped into low presenteeism-normal coping group; married with no children (OR=24.554, P=0.005) were more likely to be grouped into moderate presenteeism group; and having experienced workplace violence in the past year (OR=1.182, P=0.049) were more likely to be grouped into high presenteeism-work limitation group.There is group heterogeneity in the presenteeism of ICU nurses, and nursing managers should develop targeted interventions to reduce the presenteeism rate of ICU nurses according to the characteristics and influencing factors of each type of presenteeism of ICU nurses.